2009
DOI: 10.1037/a0016106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cognitive deficits following posterior fossa tumor resection: A neuropsychological and functional neuroimaging follow-up study.

Abstract: The posterior fossa syndrome (PFS) consists of transient cerebellar mutism, cognitive symptoms, and neurobehavioral abnormalities that typically develop in children following posterior fossa (PF) tumor resection. The pathophysiological substrate of the syndrome remains unclear. We investigated eight children of whom five presented with a variety of clinically relevant non-motor language symptoms associated with cognitive and behavioral disturbances after PF tumor resection. Four children developed transient ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 47 publications
(51 reference statements)
3
70
0
Order By: Relevance
“…A significant improvement of frontal perfusional deficits paralleled the clinical remission of mutism. These results add the view that PFS might represent a cerebello-cerebral diaschisis phenomenon, reflecting the metabolic impact of the cerebellar lesion on supratentorial cognitive and affective functions [57]. These SPECT scan findings suggest that these impairments are secondary to supratentorial metabolic hypofunction following cerebellar surgery.…”
Section: Cerebellar Mutismsupporting
confidence: 52%
See 1 more Smart Citation
“…A significant improvement of frontal perfusional deficits paralleled the clinical remission of mutism. These results add the view that PFS might represent a cerebello-cerebral diaschisis phenomenon, reflecting the metabolic impact of the cerebellar lesion on supratentorial cognitive and affective functions [57]. These SPECT scan findings suggest that these impairments are secondary to supratentorial metabolic hypofunction following cerebellar surgery.…”
Section: Cerebellar Mutismsupporting
confidence: 52%
“…Neurocognitive deficits included executive dysfunctions, concentration deficits and visuo-spatial disorders. Following Functional neuroimaging studies during the phase of mutism by means of SPECT showed perfusion deficits in the anatomo-clinically suspected supratentorial areas subserving language dynamics, syntax, naming, executive functioning, affective regulation, and behavior [57]. According to Di rocco et al pre-existing language impairment can be considered a subclinical state of Cerebellar Mutism Syndrome (CMS) in some children with posterior fossa tumor [58].…”
Section: Cerebellar Mutismmentioning
confidence: 99%
“…Individuals with intracranial tumors often suffer from various levels of physical, neuropsychological, and cognitive dysfunction during their lifetime [3][4][5][6][7] affecting their the activities of daily living (ADL), interpersonal relationships, education, work, and profession thus leading to a poor functional status and quality of life (QoL) [3][4][5] . The neuropsychiatric symptoms reported by various authors include depression [5] , mood disorders, psychotic symptoms, personality changes, disinhibition, apathy, and emotional outbreaks [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Functional neuroimaging has documented abnormalities in cerebral regions subserving language dynamics, syntax, naming, executive function, affective regulation and behavior in patients with PFS. SPECT studies have shown that the frontal perfusion deficits in patients with PFS improve in parallel to the resolution of mutism [22]. …”
Section: Introductionmentioning
confidence: 99%